PROVOCATIVE SPEECH GENRES AS A MEANS OF INDIRECT COMMUNICATION, ITS LINGUISTIC ENTITY AND ANALYSIS - V. Stepanov (Теория и практика судебной экспертизы, 2014)
In this article the system of complex and elementary provocative genres is displayed. The elementary provocative genres used to engage with each other and other communication and genre phenomena in the context of indirect communication in a sort of interference which impact on their intentionality. The provocative e!ect of the exposed provocative genres happened to be constant, and hence easily predicted, and planned.